Early and Late Complications Following Surgical Intervention for Degenerative Spondylosis - Muhammad Zahid Khan, Abdul Satar, Samir Khan Kabir, Arif Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the early and late complications following surgical interventions for degenerative spondylosis, focusing on their impact on recovery and long-term outcomes. Methodology: A retrospective analysis was conducted at the Department of Orthopedic & Spine Surgery, Hayatabad Medical Complex, Peshawar, from June 2017 to June 2022, involving 100 patients who underwent spinal surgeries for degenerative spondylosis. The sample was divided into two groups: 57 patients who underwent decompression only and 43 who underwent decompression with fusion. The study analyzed early complications (within 30 days post-surgery) and late complications (after 30 days), along with the role of comorbidities in these outcomes. Results: The study found that 45% of patients experienced early complications, including wound infections, hematomas, and nerve damage, while 55% had no early complications. For late complications, 44% of patients developed issues such as adjacent segment degeneration and pseudoarthrosis, and 56% did not experience any late complications. Comorbidities such as diabetes, hypertension, obesity, and osteoporosis were prevalent, with diabetes and hypertension significantly increasing the risk of complications (p = 0.045 for late complications). Conclusion: The study concluded that spinal surgery for degenerative spondylosis carries a substantial risk of both early and late complications, particularly in patients with comorbid conditions. These findings emphasize the importance of preoperative assessments and tailored care strategies to minimize complications and improve patient outcomes. Future research should focus on larger, multicenter studies to refine surgical techniques and further explore the relationship between comorbidities and complications in spinal surgeries. Keywords: degenerative spondylosis, spinal surgery, complications, decompression, fusion.